EMERGENCY ONLINE TEACHING DURING THE GLOBAL PANDEMIC – A REVIEW OF SELECTED CASES FROM INTERNATIONAL RESEARCH TO DATE - Kamiński, Krystian (Neofilolog, 2021)
At the beginning of 2020, educational systems around the world faced one of the greatest and most important challenges of the 21st century. Due to the global pandemic and the need to introduce social distancing rules, it was decided to close schools and switch to modes of learning that do not require physical contact between learners and teachers. This decision was associated with numerous problems and difficulties in various areas of school life and the necessity to introduce new rules. More than a year after the introduction of the new learning reality, teachers and students around the world have managed to adapt. International researchers are trying to describe this new order by asking questions about what the school looks like in the time of the pandemic, how students are doing, and what strategies teachers have adopted. The article focuses on research on education and foreign language teaching conducted in 2020 in China, South Korea, Germany, and Poland. The findings to date are combined with a brief description of the educational situation in these countries. Finally, the first conclusions and recommendations are formulated that can be drawn on the basis of data collected by international researchers.